2017
DOI: 10.1136/bcr-2016-219160
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypophosphataemia after intravenous iron administration

Abstract: Iron deficiency is common and can be effectively treated with parenteral iron infusion. We report a case of an iron-deficient and vitamin D-deficient woman who developed severe symptomatic hypophosphataemia following intravenous ferric carboxymaltose administration. We stress the need of increased awareness of this potential complication among physicians. Patients should be informed of this complication and instructed to report for follow-up if they experience new musculoskeletal symptoms or worsening of tired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 15 publications
0
31
0
1
Order By: Relevance
“…In contrast, iron-induced hypophosphataemic  osteomalacia has been reported with several formulations of parenteral iron since the 1980s, including iron saccharide,19 iron polymaltose8 and most recently as in our patient, FCM 7. A recent randomised controlled trial comparing iron dextran to FCM in women with iron deficiency anaemia secondary to heavy uterine bleeding demonstrated that although FCM causes similar decreases in inactive cFGF23, 58% of patients receiving FCM experienced a transient increase in iFGF23 and subsequent hypophosphataemia 4.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, iron-induced hypophosphataemic  osteomalacia has been reported with several formulations of parenteral iron since the 1980s, including iron saccharide,19 iron polymaltose8 and most recently as in our patient, FCM 7. A recent randomised controlled trial comparing iron dextran to FCM in women with iron deficiency anaemia secondary to heavy uterine bleeding demonstrated that although FCM causes similar decreases in inactive cFGF23, 58% of patients receiving FCM experienced a transient increase in iFGF23 and subsequent hypophosphataemia 4.…”
Section: Discussionmentioning
confidence: 60%
“…Although hypophosphatemia incidence ranged from 41% to 70% in large trials of IDA treated with FCM, it was previously thought to be asymptomatic and transient . Several cases of severe hypophosphatemia following intravenous iron administration have been reported, some after only a single dose . Symptoms of hypophosphatemia include pain, nausea, and asthenia; when severe, hypophosphatemia can result in muscle (including diaphragmatic) weakness, potentially leading to respiratory failure, and rhabdomyolysis, which could lead to acute renal failure, hemolytic anemia, and cardiac dysrhythmias .…”
Section: Discussionmentioning
confidence: 99%
“…Coincident with increased utilization of intravenous iron, reports are accumulating of patients who developed severe hypophosphatemia with serious musculoskeletal complications following their administration, including osteomalacia, fragility fractures, and hypoxemia (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Although the molecular mechanism of hypophosphatemia is not fully understood, certain forms of intravenous iron may increase circulating concentrations of fibroblast growth factor 23 (FGF23) (13)(14)(15)(16).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…While further studies are needed to investigate mechanisms of how these factors predispose to hypophosphatemia, clinicians should exercise special caution when prescribing ferric carboxymaltose to higher-risk patients. Hypophosphatemia was initially considered an uncommon, self-limited, and benign biochemical consequence of ferric carboxymaltose administration, but multiple cases with serious musculoskeletal complications have emerged (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Across these cases, the correct diagnosis of hypophosphatemia was delayed by a confluence of factors including lack of knowledge of the relationship between iron and phosphate homeostasis; low awareness of hypophosphatemia as an adverse effect of ferric carboxymaltose; failure to test serum phosphate; and misattribution of symptoms of hypophosphatemia to iron deficiency anemia or its underlying cause even when serum phosphate was measured.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%